2013
DOI: 10.1080/10503307.2013.847985
|View full text |Cite
|
Sign up to set email alerts
|

Working alliance predicts psychotherapy outcome even while controlling for prior symptom improvement

Abstract: The alliance predicts outcome over and above the effect of prior symptom improvement, supporting a reciprocal influence model of the relationship between alliance and symptom change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 39 publications
5
70
1
2
Order By: Relevance
“…There have been a limited number of studies examining the link of alliance-symptom change while taking into consideration the temporal sequence (Barber, 2009;Falkenström et al, 2014;Zilcha-Mano et al, 2014). However, the previous longitudinal reciprocal research (e.g., (Falkenström et al, 2014) investigating the effect of the working alliance typically Reciprocal Model of Working Alliance and Therapeutic Outcome 7 adopted a single alliance rating at the third session.…”
Section: Reciprocal Model Of Working Alliance and Therapeutic Outcomementioning
confidence: 99%
See 3 more Smart Citations
“…There have been a limited number of studies examining the link of alliance-symptom change while taking into consideration the temporal sequence (Barber, 2009;Falkenström et al, 2014;Zilcha-Mano et al, 2014). However, the previous longitudinal reciprocal research (e.g., (Falkenström et al, 2014) investigating the effect of the working alliance typically Reciprocal Model of Working Alliance and Therapeutic Outcome 7 adopted a single alliance rating at the third session.…”
Section: Reciprocal Model Of Working Alliance and Therapeutic Outcomementioning
confidence: 99%
“…While the previous research has consistently demonstrated the prediction of the working alliance on the therapeutic outcome (Horvath et al, 2011;Lambert & Barley, 2001), the mechanism of this effect is continuously being questioned and investigated (e.g., (Falkenström, Granström, & Holmqvist, 2014;Tasca & Lampard, 2012). Norcross and Lambert (2014) commented that psychotherapy professionals could oversimplify the nature of therapy and exaggerate the impact of the working alliance when only seeing the prominent legacy of the unidirectional alliance-outcome research.…”
Section: Reciprocal Influence Model Of Working Alliance and Therapeutmentioning
confidence: 99%
See 2 more Smart Citations
“…Para Martin, Garske e Davis (2000) esta variação conceitual é decorrente das diferentes edifi cações teóricas existentes na psicologia. Contudo, todas as abordagens ressaltam a importância da aliança terapêutica no processo psicoterápico, e entende-se que uma vez estabelecida pode gerar resultados favoráveis ao processo (Falkenström, Granström, & Homqvist, 2014;Luborsky, 2000;Yoshida & Enéas, 2013).…”
Section: Introductionunclassified